(untitled) (LEARNing Landscapes, 2012)
In this article, the authors attempt to deconstruct social work education using a metaphor of a "social work tree." Through reflective dialogue and an arts-based approach, we critically examined the past, present, and future of social work education. This collaborative art project allows us to visually express the colonial roots of social work education and the transformation that is possible when its Eurocentric stronghold is uprooted. We discuss the implications for social work education and suggest ways of moving forward with an allied approach that bridges the gap between mainstream and Indigenous social work education.